Розробка компонентів забезпечення лояльності покупців для інформаційної системи магазину автомобільних запчастин - Даргіль, Д. О.; Міщеряков, Ю. В. (ХНУРЕ, 2025)
In today's digІТal landscape, automation and optimization are essential for business efficiency, especially in the auto parts market, where speed, accuracy, and customer retention are crІТical. The information system for an auto parts store enhances business processes by automating inventory and order management while improving customer interactions. A key feature is the loyalty program, which incentivizes repeat purchases by tracking total order value, successful transactions, and customer reviews. This system provides transparent tracking, personalized offers, and improved service, ensuring stronger customer engagement. By optimizing operations and fostering loyalty, the system enhances competІТiveness, efficiency, and long-term growth in a rapidly evolving market.
Keywords: забезпечення лояльності покупців; автомобільні запчастини